Identifikasi Bakteri Pada Serasah Daun Mangrove yang Terdekomposisi di Kawasan Konservasi Mangrove dan Bekantan (KKMB) Kota Tarakan - Y. Yulma; Burhanuddin Ihsan; S. Sunarti; Eka Malasari; Neny Wahyuni; M. Mursyban (Journal of Tropical Biodiversity and Biotechnology, 2017)
Bacteria in mangrove ecosystem has a significant role in litter decomposition that is essential to provide organic nutrition for organisms in mangrove forest. The research was aimed to identify decomposition bacteria that exist in KKMB Tarakan mangrove conservation area. The identification focused on litters from several mangrove vegetation, which are Bruguiera parviflora, Rhizophora apiculata, Sonneratia alba, dan Avicennia alba. The method used was explorative descriptive while testing parameter was genus. The research identified seven bacteria genera for litter from Bruguiera parviflora which are Bacillus, Aeromonas, Nocardiae, Corynebacterium, Listeria, Bacteroides, Pseudomonas. Six genera from Rhizophora apiculata which are Bacillus, Listeria, Enterobacteria, Aeromonas, Actinobacilus, and Bacteroides. Five genera for Sonneratia alba which are Bacillus, Aeromonas, Listeria, Enterobacteria, Staphylococcus. Also eight genera from Avicennia alba which are Bacillus, Clostridium, Enterobacteria, Bacteroides, Plesiomonas, Bordella, Streptococcus, and Neisseria. The results conclude that different species of mangrove vegetation attracts different species of bacteria as well.